DAMPAK WOMEN’S CAREER DEVELOPMENT MODELS PADA CAREER SUCCESS ORIENTATION BEHAVIOR (Studi Pada Wanita Karier Kota Denpasar Bali) - Komalasari, Yeyen (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2020)
The purpose of this study was to find out the behavior of women's career success orientation, based on Women's Career Development Models. Various organizations have recognized the ability to carry out their duties and responsibilities, so this support makes them able to decide on carreer success orientation (career goals). The research method is a qualitative method with an interpretative phenomenology approach. Data extraction techniques use in-depth interviews on 6 career women informants in Denpasar City. The conclusion; 1) idealistic achievement model who is willing to achieve by getting challenging that increase their career, 2) pragmatic endurance models are mid-career women who are at the point of choosing family or professional responsibilities, so that they are more careful and stay away from achievement but still work well. and 3) re-inventive contribution models for women in their final careers, they don't think about achievement anymore, but see their careers as opportunities to share and be useful to others. Therefore, it is recommended in determining to choose a career path, it should consider to career success orientation according to the different phases of career women life cycle.